2020
DOI: 10.1002/csc2.20302
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of stay‐green, yield, and agronomic traits in spring wheat

Abstract: Hard red spring wheat (Triticum aestivum L.) grown in rainfed environments in the northern Great Plains of North America frequently encounter drought and heat stress during grain-fill, thus reducing yield. Delayed leaf senescence after heading, known as the stay-green trait, has been found to help spring wheat tolerate drought and heat stress during grain-fill. To better understand how the staygreen trait relates to expression of other agronomic traits, data was analyzed from a recombinant inbred line (RIL) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Compared with the individual maps, three other TKW QTLs were stably identified using the consensus map (Table 7), i.e., qTKW-1B-2, qTKW-2D-2, and qTKW-6B-3, which were in similar positions as those reported by Gerard et al (2019), Zhang et al (2020c), andCook et al (2021), respectively.…”
Section: Comparison Of the Detected Qtls With Studies On Other Mapping Populationsmentioning
confidence: 70%
“…Compared with the individual maps, three other TKW QTLs were stably identified using the consensus map (Table 7), i.e., qTKW-1B-2, qTKW-2D-2, and qTKW-6B-3, which were in similar positions as those reported by Gerard et al (2019), Zhang et al (2020c), andCook et al (2021), respectively.…”
Section: Comparison Of the Detected Qtls With Studies On Other Mapping Populationsmentioning
confidence: 70%
“…Previous studies have demonstrated that unlike the cosmetic stay-green phenotype, the functional stay-green phenotype usually involves multiple metabolic pathways and is controlled by many loci (Cook et al, 2021;Ren et al, 2022). The difference in leaf senescence between CN17 and CN19 is very conspicuous, especially in the later grain filling stage; therefore, despite their genetic background being different, as demonstrated by a pedigree analysis, these cultivars were used to detect DEGs (Li et al, 2017).…”
Section: Identification Of Key Genes Responsible For the Functional S...mentioning
confidence: 99%
“…Statistical analysis. Since all wheat genotypes, except for the checks, had not been previously tested at the Siirt location, the genotypic effect was considered random in the analysis of variance (ANOVA) (Cook et al 2021). The ANOVA, t-test, and descriptive statistics for each variable (EGC, VS, and GY) measured in this experiment, which was conducted based on the ARCBD, and the correlation analysis between the variables were performed using SAS software (Wolfinger et al 1997;Kling & Merk 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As the genotypes tested in the first season were different from those tested in the second season, the significance levels of the differences between the variables measured over seasons were determined by the t-test. The broad sense heritability (H 2 ) values were predicted by the best linear unbiased predictor (BLUP) statistical method (Cullis et al 2006;Cook et al 2021;Kling & Merk 2021).…”
Section: Methodsmentioning
confidence: 99%